Inklusi Digital dan Pemberdayaan UMKM Lampung Tengah: Meningkatkan Daya Saing Usaha Mikro, Kecil, dan Menengah di Era Digital - Rudihartati, Leny; Ferdiansyah, Muhammad; Rahman, Taufik (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
The Community Service Program (PKM) titled "Strengthening Local Economy Through Information Technology Training for Micro, Small, and Medium Enterprises (MSMEs)" was conducted at Yunanis Snack in Purnama Tunggal Village, Central Lampung, with the primary objective of enhancing the capacity of MSMEs to utilize information technology and develop digital marketing strategies. Initial identification revealed significant challenges, including limited marketing reach, low production capacity, and inadequate digital literacy among employees. Through a structured intervention involving digital marketing training, the development of an official website, and the provision of modern production equipment, this program successfully increased production efficiency by 30% and expanded marketing outreach. Ongoing monitoring and evaluation demonstrated an increase in sales and positive feedback from partners regarding the training received. However, challenges related to website maintenance and technical skill acquisition remain to be addressed to ensure the program's sustainability. Overall, the outcomes of this PKM not only positively impacted Yunanis Snack but also contributed to the strengthening of the local economy in Purnama Tunggal Village. This program is expected to serve as an inspirational model for other MSMEs in leveraging information technology as a strategic tool for sustainable economic growth.